Risk Analysis of Lifeline Infrastructures Threaten By Landslide - Norhaidi, Ummi Anisah (Universiti Teknologi PETRONAS, 2017)
Landslide in general a movement of a soil mass due to specific mechanics of slope failure. The factors triggering landslide could be natural causes or it could also be under the influence of human activities. Different landslide types contributes to different types of effects to property, injury and even death. Commonly effects of landslide in Malaysia are fatalities, serious injuries and infrastructure and structure destruction. The major part to be considered is the restoration activities that will be done after the occurrence of the natural events. Restoration activities could be costly and it will also impacts the economy of a country. The occurrence of landslide could not be stop. However, preventive way could be considered, by analyzing the stability of the slope.